Epstein‐Barr virus antibody titer as a stress biomarker and its association with social capital in rural Fujian communities, China. Issue 4 (11th May 2018) - Yazawa, Aki; Inoue, Yosuke; Cai, Guoxi; Tu, Raoping; Huang, Meng; He, Fei; Chen, Jie; Yamamoto, Taro; Watanabe, Chiho
Abstract: Objectives: There has been little research on the association between social capital and psychological stress measured by a biomarker, particularly in developing countries. Our objective was to investigate the association between Epstein‐Barr virus (EBV) antibody titer, an indicator of cellular immune function previously shown to be associated with psychological stress, and social capital among rural community dwellers in Fujian Province, China. Methods: We conducted a cross‐sectional survey in seven rural communities in Fujian in 2015. We used questionnaire data and dried blood spot samples for the measurement of biomarkers collected from 734 local residents for the analysis. We conducted a mixed effects regression analysis to investigate the association between EBV antibody titer and four social capital variables, which included cognitive and structural social capital assessed both at individual and community levels. Results: Community‐level structural social capital was inversely associated with psychological stress (coefficient = −0.96, 95% confidence interval [CI] = −1.91, −0.01) while individual‐level structural social capital was positively associated with it (coefficient = 0.21, 95% CI = 0.07, 0.36). Neither individual‐ nor community‐level cognitive social capital was associated with psychological stress status. Conclusions: In rural Fujian, China, social capital seemed to be an important determinant of psychological health. While living in a community with active social interaction may benefit the residents psychologically, social interaction in the form of strongly bonded relationships may be a source of psychological stress at the individual level due to the potential demands and obligations that may be associated with such connections.